OsNRAMP5 Is a Major Transporter for Lead Uptake in Rice - Chang, Jia-Dong; Gao, Weiping; Wang, Peng; Zhao, Fang-Jie (Environmental science & technology, 2022)
Lead (Pb) is one of the most toxic metals affecting human health globally. Food is an important source of chronic Pb exposure in humans. How Pb is taken up by rice, a staple food for over half of the global population, remains unknown. In the present study, we investigated the role of OsNRAMP5, a member of the NRAMP (Natural Resistance-Associated Macrophage Protein) transporter family, in Pb uptake by rice roots. Heterologous expression of OsNRAMP5 in yeast increased Pb uptake and sensitivity toward Pb. Knockout of OsNRAMP5 in rice by CRISPR/Cas9 gene editing resulted in significant decreases in root uptake of Pb and accumulation in rice shoots. The maximum influx velocity (V max) for Pb uptake of the knockout mutants was 70% lower than that of wild-type plants. When grown in Pb-contaminated paddy soil, OsNRAMP5 knockout mutants accumulated approximately 50 and 70% lower Pb concentrations in the grain and straw, respectively, than the wild type. OsNRAMP5 expression in rice roots was not affected by Pb exposure. These results indicate that OsNRAMP5 is a major transporter for Pb uptake in rice, in addition to its role in the uptake of manganese and cadmium. This study provides a mechanistic understanding of Pb uptake in rice plants and a potential strategy to limit Pb accumulation in rice grains.